Answer:
The two equations given in the question are:
3y = 4x + 7
- 4x - 4y = 28
Now, let us subtract 3y and 7 from both sides of the first equation
3y - 3y - 7 = 4x + 7 - 3y - 7
- 7 = 4x - 3y
This can be written as
4x - 3y = - 7
Now let us set the two equations in table form
4x - 3y = - 7
- 4x - 4y = 28
We get from the above deduction,
- 7y = 21
y = - 21/7
y = - 3
Now let us put the value of y in the first equation, we get
3y = 4x + 7
3 (- 3) = 4x + 7
- 9 = 4x + 7
4x = - 9 - 7
4x = - 16
x - - 4
So (x,y) comes out to be (-4, -3). The correct option among all the options given in the question is the first option or option "A".
please add options